Pengaruh Penggunaan Strategi Active Knowledge Sharing Terhadap Hasil Belajar Matematika Siswa Kelas VIII SMP N 1 2X11 Kayutanam (Indo-MathEdu Intellectuals Journal, 2024)
This research was motivated by the problems found in class VIII SMPN 1 2x11 Kayutanam, namely low student learning outcomes, lack of student knowledge about the material being taught, lack of active involvement of students in the learning process. The aim of this research is to find out that students' mathematics learning outcomes using the Active Knowledge Sharing strategy are better than student learning outcomes using conventional learning. This type of research is pre-experimental research with a research design, namely The Static Group Comparison Design. The population in this study were all students in class VIII of SMP N 1 2X11 Kayutanam. The sample in this research was class VIII.1 students as the experimental class and class VIII.2 students as the control class. The instrument used is an essay test. Based on the results of the final test analysis calculated using the t-test, tcount = 5.04 and ttable = 1.67. Because tcount > ttable. So, reject H0 and accept H1. So, it can be concluded that students' mathematics learning outcomes using the Active Knowledge Sharing strategy are better than student learning outcomes using conventional learning in class VIII SMP N 1 2x11 Kayutanam Academic Year 2022/2023